PJMHS 2022
DOI: 10.53350/pjmhs22165823
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Emotional Intelligence and Leadership Style among Nurse Managers

Abstract: Objectives: The study aims at assessing the level of emotional intelligence as well as leadership styles and detecting the relationship between emotional intelligence and leadership styles. Materials and methods: A descriptive study, correlational design that is initiated for the period of October 1st 2021 to June 1st, 2022. The sample of the study includes 260 nurse managers was selected by convenient sampling method (non-probability sample). The setting of the study includes the teaching hospitals in Baghdad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Also majority of those head nurses had high overall levels and mean scores for each emotional intelligence subscale including emotional self-awareness, expression, awareness of others, reasoning, self-management, management of others, self-control and social skills. This result is supported by (23) study correlation between emotional intelligence and leadership style among nurse mangers. They found that nurse managers are associated with high level of emotional intelligence and good leadership competencies.…”
Section: Discussionsupporting
confidence: 58%
“…Also majority of those head nurses had high overall levels and mean scores for each emotional intelligence subscale including emotional self-awareness, expression, awareness of others, reasoning, self-management, management of others, self-control and social skills. This result is supported by (23) study correlation between emotional intelligence and leadership style among nurse mangers. They found that nurse managers are associated with high level of emotional intelligence and good leadership competencies.…”
Section: Discussionsupporting
confidence: 58%